Investigating the influence of organizational culture on competitive advantage through the mediating role of Entrepreneurial orientation - Tessema, Dagnu Haile; Assefa, Hannan Ketama (PT Mattawang Mediatama Solution, 2025)
The purpose of this research is to examine the effect of organizational culture (OC) on competitive advantage (CA) and the mediating role of entrepreneur orientation (EO) by utilizing resource-based views and dynamic capability theory in the hotel industry of Ethiopia. Structured questionnaires were administered, and data was drawn from (N = 180) managers of 65 hotels in Ethiopia through convenience sampling. The collected data was analyzed using Smart-PLS 4. The findings of this study indicated that OC significantly influences CA and EO partially mediates this relationship. Moreover, entrepreneurial orientation has a positive and significant influence on competitive advantage. The current research has an immense contribution for policymakers and managers of the tourism industry, mainly hotels, to foster competitive advantage through managerial interventions. This study will be a pioneering attempt to investigate the influence of organizational culture on competitive advantage, both directly and indirectly, through the mediating role of entrepreneurial orientation, employing resource-based views and dynamic capability theory.